2023
DOI: 10.1093/nar/gkad260
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic mechanism and pH dependence of a methyltransferase ribozyme (MTR1) from computational enzymology

Abstract: A methyltransferase ribozyme (MTR1) was selected in vitro to catalyze alkyl transfer from exogenous O6-methylguanine (O6mG) to a target adenine N1, and recently, high-resolution crystal structures have become available. We use a combination of classical molecular dynamics, ab initio quantum mechanical/molecular mechanical (QM/MM) and alchemical free energy (AFE) simulations to elucidate the atomic-level solution mechanism of MTR1. Simulations identify an active reactant state involving protonation of C10 that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 72 publications
2
11
0
Order By: Relevance
“…Recently, an MTR1 has evolved in vitro that binds O 6 -methylguanine and catalyzes the methylation of a target adenine (A63) at the N1 position , (Figure a). Computational enzymology studies performed by our group, in collaboration with Huang, Lilley, and co-workers, revealed a surprisingly sophisticated mechanism that involves a protonated cytosine residue that acts as an acid to facilitate site-specific C–N bond formation, broadening the range of known RNA-catalyzed chemistry and further demonstrating the versatility of RNA catalysis . In the computational study, we employed an early version of the string method and found it to be slowly convergent, making it extremely costly to perform ab initio QM/MM simulations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, an MTR1 has evolved in vitro that binds O 6 -methylguanine and catalyzes the methylation of a target adenine (A63) at the N1 position , (Figure a). Computational enzymology studies performed by our group, in collaboration with Huang, Lilley, and co-workers, revealed a surprisingly sophisticated mechanism that involves a protonated cytosine residue that acts as an acid to facilitate site-specific C–N bond formation, broadening the range of known RNA-catalyzed chemistry and further demonstrating the versatility of RNA catalysis . In the computational study, we employed an early version of the string method and found it to be slowly convergent, making it extremely costly to perform ab initio QM/MM simulations.…”
Section: Resultsmentioning
confidence: 99%
“…The ff99OL3 RNA force field and Joung and Cheatham monovalent ion parameters have been used. Details regarding the preparation and equilibration of this system have already been reported elsewhere . In brief, the pressure and temperature were equilibrated for 50 ns with the MM force field potential to maintain 1 atm and 298 K in the isothermal–isobaric ensemble using the Berendsen barostat and Langevin thermostat with a collision frequency of 5 ps –1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of the current shortcomings in force field accuracy and reliability and in the development of enhanced sampling schemes that would allow also modeling large conformational changes and molecular RNA/RNA, protein/RNA, and drug/RNA recognition events with increased accuracy, remarkable examples exist of all-atoms simulations studies of complex RNA-only and protein/RNA machineries. , …”
Section: Discussionmentioning
confidence: 99%
“…The discovery of ribozymes in the early 1980s added another important hypothesis that might explain the origin of life on Earth. Within that so-called “RNA World hypothesis”, the catalytic function of ribozymes is crucial in addition to storing and replicating information such that protein synthesis by the ribosome evolved. Since then, an overwhelmingly large number of experimental and theoretical studies have been devoted to investigating the structure, dynamics, and functions of various ribozymes. Ribozymes are found to be involved in many biological reactions such as processing of tRNA, controlling of gene expression to treat diseases such as metabolic disorder, viral infections and cancer, and splicing of mRNAs. Notably, the hairpin ribozyme (HpRz) is one of the major naturally occurring ribozymes capable of catalyzing self-cleavage transesterification reactions at the RNA backbone. The hairpin ribozyme belongs to the distinct class of “G+A” ribozymes, characterized by shared structural motifs and functional properties, connecting it to an intricate lineage that includes other ribozymes such as VS and Twister, all sharing a common L-platform/L-scaffold active site architecture .…”
mentioning
confidence: 99%